A Multiple Piccolino-RIBEYE Interaction Supports Plate-Shaped Synaptic Ribbons in Retinal Neurons - Müller, Tanja; Gierke, Kaspar; Joachimsthaler, Anneka; Sticht, Heinrich; Izsvak, Zsuzsanna; Hamra, F. Kent; Fejtová, Anna; Ackermann, Frauke; Garner, Craig C.; Kremers, Jan; Brandstätter, Johann Helmut; Regus-Leidig, Hanna (Journal of Neuroscience, 2019)
Active zones at chemical synapses are highly specialized sites for the regulated release of neurotransmitters. Despite a high degree of active zone protein conservation in vertebrates, every type of chemical synapse expresses a given set of protein isoforms and splice variants adapted to the demands on neurotransmitter release. So far, we know little about how specific active zone proteins contribute to the structural and functional diversity of active zones. In this study, we explored the nanodomain organization of ribbon-type active zones by addressing the significance of Piccolino, the ribbon synapse-specific splice variant of Piccolo, for shaping the ribbon structure. We followed up on previous results, which indicated that rod photoreceptor synaptic ribbons lose their structural integrity in a knockdown of Piccolino. Here, we demonstrate an interaction between Piccolino and the major ribbon component RIBEYE that supports plate-shaped synaptic ribbons in retinal neurons. In a detailed ultrastructural analysis of three different types of retinal ribbon synapses in Piccolo/Piccolino-deficient male and female rats, we show that the absence of Piccolino destabilizes the superstructure of plate-shaped synaptic ribbons, although with variable manifestation in the cell types examined. Our analysis illustrates how the expression of a specific active zone protein splice variant (e.g., Piccolino) contributes to structural diversity of vertebrate active zones.
CRIS-Team WoS Importer:2019-04-12

Analysis of RIM Expression and Function at Mouse Photoreceptor Ribbon Synapses - Löhner, Martina; Babai, Norbert; Müller, Tanja; Gierke, Kaspar; Atorf, Jenny; Joachimsthaler, Anneka; Peukert, Angela; Martens, Henrik; Feigenspan, Andreas; Kremers, Jan; Schoch, Susanne; Brandstätter, Johann Helmut; et al. (The Journal of Neuroscience, 2017)
RAB3A-interacting molecule (RIM) proteins are important regulators of transmitter release from active zones. At conventional chemical synapses, RIMs contribute substantially to vesicle priming and docking and their loss reduces the readily releasable pool of synaptic vesicles by up to 75%. The priming function of RIMs is mediated via the formation of a tripartite complex with Munc13 and RAB3A, which brings synaptic vesicles in close proximity to Ca(2+) channels and the fusion site and activates Munc13. We reported previously that, at mouse photoreceptor ribbon synapses, vesicle priming is Munc13 independent. In this study, we examined RIM expression, distribution, and function at male and female mouse photoreceptor ribbon synapses. We provide evidence that RIM1? and RIM1? are highly likely absent from mouse photoreceptors and that RIM2? is the major large RIM isoform present at photoreceptor ribbon synapses. We show that mouse photoreceptors predominantly express RIM2 variants that lack the interaction domain for Munc13. Loss of full-length RIM2? in a RIM2? mutant mouse only marginally perturbs photoreceptor synaptic transmission. Our findings therefore strongly argue for a priming mechanism at the photoreceptor ribbon synapse that is independent of the formation of a RIM-Munc13-RAB3A complex and thus provide further evidence for a fundamental difference between photoreceptor ribbon synapses and conventional chemical synapses in synaptic vesicle exocytosis.SIGNIFICANCE STATEMENT RAB3A-interacting molecules 1 and 2 (RIM1/2) are essential regulators of exocytosis. At conventional chemical synapses, their function involves Ca(2+) channel clustering and synaptic vesicle priming and docking through interactions with Munc13 and RAB3A, respectively. Examining wild-type and RIM2 mutant mice, we show here that the sensory photoreceptor ribbon synapses most likely lack RIM1 and predominantly express RIM2 variants that lack the interaction domain for Munc13. Our findings demonstrate that the photoreceptor-specific RIM variants are not essential for synaptic vesicle priming at photoreceptor ribbon synapses, which represents a fundamental difference between photoreceptor ribbon synapses and conventional chemical synapses with respect to synaptic vesicle priming mechanisms.
EVALuna2:21339

Angiotensin-Receptor-Associated Protein Modulates Ca2+ Signals in Photoreceptor and Mossy Fiber cells - Barro-Soria, Rene; Caicedo, Alejandro; Jaegle, Herbert; Merkel, Laura; Zhao, Na; Knop, Gabriel; Gierke, Kaspar; Dannullis, Andrea; Castrop, Hayo; Brandstätter, Johann Helmut; Kirchhoff, Frank; Feigenspan, Andreas; et al. (Scientific Reports, 2019)
Fast, precise and sustained neurotransmission requires graded Ca2+ signals at the presynaptic terminal. Neurotransmitter release depends on a complex interplay of Ca2+ fluxes and Ca2+ buffering in the presynaptic terminal that is not fully understood. Here, we show that the angiotensin-receptor-associated protein (ATRAP) localizes to synaptic terminals throughout the central nervous system. In the retinal photoreceptor synapse and the cerebellar mossy fiber-granule cell synapse, we find that ATRAP is involved in the generation of depolarization-evoked synaptic Ca2+ transients. Compared to wild type, Ca2+ imaging in acutely isolated preparations of the retina and the cerebellum from ATRAP knockout mice reveals a significant reduction of the sarcoendoplasmic reticulum (SR) Ca2+-ATPase (SERCA) activity. Thus, in addition to its conventional role in angiotensin signaling, ATRAP also modulates presynaptic Ca2+ signaling within the central nervous system.
CRIS-Team WoS Importer:2020-02-07

Functional and Structural Development of Mouse Cone Photoreceptor Ribbon Synapses - Davison, Adam; Gierke, Kaspar; Brandstätter, Johann Helmut; Babai, Norbert (Investigative Ophthalmology & Visual Science, 2022)
PURPOSE. Cone photoreceptors of the retina use a sophisticated ribbon-containing synapse to convert light-dependent changes in membrane potential into release of synaptic vesicles (SVs). We aimed to study the functional and structural maturation of mouse cone photoreceptor ribbon synapses during postnatal development and to investigate the role of the synaptic ribbon in SV release. METHODS. We performed patch-clamp recordings from cone photoreceptors and their postsynaptic partners, the horizontal cells during postnatal retinal development to reveal the functional parameters of the synapses. To investigate the occurring structural changes, we applied immunocytochemistry and electron microscopy. RESULTS. We found that immature cone photoreceptor terminals were smaller, they had fewer active zones (AZs) and AZ-anchored synaptic ribbons, and they produced a smaller Ca2+ current than mature photoreceptors. The number of postsynaptic horizontal cell contacts to synaptic terminals increased with age. However, tonic and spontaneous SV release at synaptic terminals stayed similar during postnatal development. Multiquantal SV release was present in all age groups, but mature synapses produced larger multiquantal events than immature ones. Remarkably, at single AZs, tonic SV release was attenuated during maturation and showed an inverse relationship with the appearance of anchored synaptic ribbons. CONCLUSIONS. Our developmental study suggests that the presence of synaptic ribbons at the AZs attenuates tonic SV release and amplifies multiquantal SV release. However, spontaneous SV release may not depend on the presence of synaptic ribbons or voltage-sensitive Ca2+ channels at the AZs.
CRIS-Team Scopus Importer:2022-04-15
Keywords: cone photoreceptor; development; retina; ribbon synapse; synaptic vesicle release

Genetic disruption of bassoon in two mutant mouse lines causes divergent retinal phenotypes - Ryl, Miriam; Urbasik, Alexander; Gierke, Kaspar; Babai, Norbert; Joachimsthaler, Anneka; Feigenspan, Andreas; Frischknecht, Renato; Stallwitz, Nina; Fejtová, Anna; Kremers, Jan; von Wittgenstein, Julia; Brandstätter, Johann Helmut (The FASEB Journal, 2021)
Bassoon (BSN) is a presynaptic cytomatrix protein ubiquitously present at chemical synapses of the central nervous system, where it regulates synaptic vesicle replenishment and organizes voltage-gated Ca2+ channels. In sensory photoreceptor synapses, BSN additionally plays a decisive role in anchoring the synaptic ribbon, a presynaptic organelle and functional extension of the active zone, to the presynaptic membrane. In this study, we functionally and structurally analyzed two mutant mouse lines with a genetic disruption of Bsn-Bsngt and Bsnko -using electrophysiology and high-resolution microscopy. In both Bsn mutant mouse lines, full-length BSN was abolished, and photoreceptor synaptic function was similarly impaired, yet synapse structure was more severely affected in Bsngt/gt than in Bsnko/ko photoreceptors. The synaptic defects in Bsngt/gt retina coincide with remodeling of the outer retina-rod bipolar and horizontal cell sprouting, formation of ectopic ribbon synaptic sites-and death of cone photoreceptors, processes that did not occur in Bsnko/ko retina. An analysis of Bsngt/ko hybrid mice revealed that the divergent retinal phenotypes of Bsngt/gt and Bsnko/ko mice can be attributed to the expression of the Bsngt allele, which triggers cone photoreceptor death and neurite sprouting in the outer retina. These findings shed new light on the existing Bsn mutant mouse models and might help to understand mechanisms that drive photoreceptor death.
CRIS-Team Scopus Importer:2021-04-16
Keywords: active zone; bassoon; photoreceptor; photoreceptor death; ribbon synapse

Heterogeneous presynaptic distribution of munc13 isoforms at retinal synapses and identification of an unconventional bipolar cell type with dual expression of munc13 isoforms: A study using munc13-exfp knock-in mice - Gierke, Kaspar; von Wittgenstein, Julia; Hemmerlein, Maike; Atorf, Jenny; Joachimsthaler, Anneka; Kremers, Jan; Cooper, Benjamin H.; Varoqueaux, Frederique; Regus-Leidig, Hanna; Brandstätter, Johann Helmut (International Journal of Molecular Sciences, 2020)
Munc13 isoforms are constituents of the presynaptic compartment of chemical synapses, where they govern important steps in preparing synaptic vesicles for exocytosis. The role of Munc13-1,-2 and-3 is well documented in brain neurons, but less is known about their function and distribution among the neurons of the retina and their conventional and ribbon-type chemical synapses. Here, we examined the retinae of Munc13-1-,-2-, and-3-EXFP knock-in (KI) mice with a combination of immunocytochemistry, physiology, and electron microscopy. We show that knock-in of Munc13-EXFP fusion proteins did not affect overall retinal anatomy or synapse structure, but slightly affected synaptic transmission. By labeling Munc13-EXFP KI retinae with specific antibodies against Munc13-1,-2 and-3, we found that unlike in the brain, most retinal synapses seem to operate with a single Munc13 isoform. A surprising exception to this rule was type 6 ON bipolar cells, which expressed two Munc13 isoforms in their synaptic terminals, ubMunc13-2 and Munc13-3. The results of this study provide an important basis for future studies on the contribution of Munc13 isoforms in visual signal processing in the mammalian retina.
CRIS-Team Scopus Importer:2020-11-06
Keywords: BrMunc13-2; Conventional synapse; Munc13-1; Munc13-3; Retina; Ribbon synapse; Type 6 ON bipolar cell; UbMunc13-2

Signal transmission at invaginating cone photoreceptor synaptic contacts following deletion of the presynaptic cytomatrix protein Bassoon in mouse retina - Babai, Norbert; Gierke, Kaspar; Müller, Tanja; Regus-Leidig, Hanna; Brandstätter, Johann Helmut; Feigenspan, Andreas (Acta Physiologica, 2019)
Aim: A key feature of the mammalian retina is the segregation of visual information in parallel pathways, starting at the photoreceptor terminals. Cone photoreceptors establish synaptic contacts with On bipolar and horizontal cells at invaginating, ribbon-containing synaptic sites, whereas Off bipolar cells form flat, non-ribbon-containing contacts. The cytomatrix protein Bassoon anchors ribbons at the active zone, and its absence induces detachment of ribbons from the active zone. In this study we investigate the impact of a missing Bassoon on synaptic transmission at the first synapse of the visual system. Methods: Release properties of cone photoreceptors were studied in wild-type and mutant mouse retinae with a genetic disruption of the presynaptic cytomatrix protein Bassoon using whole-cell voltage-clamp recordings. Light and electron microscopy revealed the distribution of Ca2+ channels and synaptic vesicles, respectively, in both mouse lines. Results: Whole-cell recordings from postsynaptic horizontal cells of the two mouse lines showed that the presence of Bassoon (and a ribbon) enhanced the rate of exocytosis during tonic and evoked release by increasing synaptic vesicle pool size and replenishment rate, while at the same time slowing synaptic vesicle release. Furthermore, the number of Cav1.4 channels and synaptic vesicles was significantly higher at wild-type than at Bassoon mutant synaptic sites. Conclusion: The results of our study demonstrate that glutamate release from cone photoreceptor terminals can occur independent of a synaptic ribbon, but seems restricted to active zones, and they show the importance of a the synaptic ribbon in sustained and spatially and temporally synchronized neurotransmitter release.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Bassoon; cone photoreceptor; horizontal cell; retina; ribbon synapse; signal transmission

Synaptic vesicle release during ribbon synapse formation of cone photoreceptors - Davison, Adam; Gierke, Kaspar; Brandstätter, Johann Helmut; Babai, Norbert (Frontiers in Cellular Neuroscience, 2022)
Mammalian cone photoreceptors enable through their sophisticated synapse the high-fidelity transfer of visual information to second-order neurons in the retina. The synapse contains a proteinaceous organelle, called the synaptic ribbon, which tethers synaptic vesicles (SVs) at the active zone (AZ) close to voltage-gated Ca2+ channels. However, the exact contribution of the synaptic ribbon to neurotransmission is not fully understood, yet. In mice, precursors to synaptic ribbons appear within photoreceptor terminals shortly after birth as free-floating spherical structures, which progressively elongate and then attach to the AZ during the following days. Here, we took advantage of the process of synaptic ribbon maturation to study their contribution to SV release. We performed whole-cell patch-clamp recordings from cone photoreceptors at three postnatal (P) development stages (P8–9, P12–13, >P30) and measured evoked SV release, SV replenishment rate, recovery from synaptic depression, domain organization of voltage-sensitive Ca2+ channels, and Ca2+-sensitivity of exocytosis. Additionally, we performed electron microscopy to determine the density of SVs at ribbon-free and ribbon-occupied AZs. Our results suggest that ribbon attachment does not organize the voltage-sensitive Ca2+ channels into nanodomains or control SV release probability. However, ribbon attachment increases SV density at the AZ, increases the pool size of readily releasable SVs available for evoked SV release, facilitates SV replenishment without changing the SV pool refilling time, and increases the Ca2+- sensitivity of glutamate release.
CRIS-Team Scopus Importer:2022-12-02
Keywords: calcium; cone photoreceptor; development; pool size; retina; ribbon synapse; synaptic vesicle release

The absence of functional bassoon at cone photoreceptor ribbon synapses affects signal transmission at Off cone bipolar cell contacts in mouse retina - Babai, Norbert; von Wittgenstein, Julia; Gierke, Kaspar; Brandstätter, Johann Helmut; Feigenspan, Andreas (Acta Physiologica, 2020)
Aim: Off cone bipolar cells of the mammalian retina connect to cone photoreceptor synaptic terminals via non-invaginating flat contacts at a considerable distance from the only established neurotransmitter release site so far, the synaptic ribbon. Diffusion from the ribbon synaptic active zone is considered the most likely mechanism for the neurotransmitter glutamate to reach postsynaptic receptors on the dendritic tips of Off cone bipolar cells. We used a mutant mouse with functionally impaired photoreceptor ribbon synapses to investigate the importance of intact ribbon synaptic active zones for signal transmission at Off cone bipolar cell contacts. Methods: Whole-cell patch-clamp recordings from Off cone bipolar cells in a horizontal slice preparation of wildtype (Bsnwt) and mutant (BsnΔEx4/5) mouse retina were applied to investigate signal transmission between cone photoreceptors and Off cone bipolar cells. The distribution of postsynaptic glutamate receptors in Off cone bipolar cell dendrites was studied using multiplex immunocytochemistry. Results: Tonic synaptic activity and evoked release were significantly reduced in mutant animals. Vesicle replenishment rates and the size of the readily releasable pool were likewise decreased. The precisely timed transient current response to light offset changed to a sustained response in the mutant, exemplified by random release events only loosely time-locked to the stimulus. The kainate receptor distribution in postsynaptic Off cone bipolar cell dendritic contacts in BsnΔEx4/5 mice was largely disturbed. Conclusion: Our results suggest a major role of functional ribbon synaptic active zones for signal transmission and postsynaptic glutamate receptor organization at flat Off cone bipolar cell contacts.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Bassoon; cone photoreceptor; Off cone bipolar cell; retina; ribbon synapse; signal transmission

The first synapse in vision in the aging mouse retina - Gierke, Kaspar; Lux, Uwe; Regus-Leidig, Hanna; Brandstätter, Johann Helmut (Frontiers in Cellular Neuroscience, 2023)
Vision is our primary sense, and maintaining it throughout our lifespan is crucial for our well-being. However, the retina, which initiates vision, suffers from an age-related, irreversible functional decline. What causes this functional decline, and how it might be treated, is still unclear. Synapses are the functional hub for signal transmission between neurons, and studies have shown that aging is widely associated with synaptic dysfunction. In this study, we examined the first synapse of the visual system – the rod and cone photoreceptor ribbon synapse – in the mouse retina using light and electron microscopy at 2–3 months, 1 year, and >2 years of age. We asked, whether age-related changes in key synaptic components might be a driver of synaptic dysfunction and ultimately age-related functional decline during normal aging. We found sprouting of horizontal and bipolar cells, formation of ectopic photoreceptor ribbon synapses, and a decrease in the number of rod photoreceptors and photoreceptor ribbon synapses in the aged retina. However, the majority of the photoreceptors did not show obvious changes in the structural components and protein composition of their ribbon synapses. Noteworthy is the increase in mitochondrial size in rod photoreceptor terminals in the aged retina.
CRIS-Team Scopus Importer:2023-12-01
Keywords: aging; ectopic synapses; mitochondrial alterations; photoreceptor degeneration; retina remodeling; ribbon synapse